2016
DOI: 10.1007/s10071-016-1017-y
|View full text |Cite
|
Sign up to set email alerts
|

Kea cooperate better with sharing affiliates

Abstract: Controlled studies that focus on intraspecific cooperation tasks have revealed striking similarities, but also differences, in abilities across taxa as diverse as primates, fish, and birds. Such comparisons may provide insight into the specific socio-ecological selection pressures that led to the evolution of cooperation. Unfortunately, however, compared to primates data on birds remain relatively scarce. We tested a New Zealand psittaciform, the kea, in a dyadic cooperation task using the loose-string design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 60 publications
1
66
5
Order By: Relevance
“…In capuchins monkey ( Cebus apella ), prosocial tendencies increase with social closeness (de Waal, Leimgruber, & Greenberg, ). In keas ( Nestor notabilis ), when tested in a loose‐string paradigm where birds had to cooperate to obtain a reward, birds cooperated more with affiliates and were also more successful when tested with affiliates than with non‐affiliates (Schwing, Jocteur, Wein, Noë, & Massen, ). In birds, affiliative interactions can be easily measured by recording allopreening and maintenance of close proximity (Seibert, ), as observed in captive groups of spectacled parrotlets ( Forpus conspicillatus ; Garnetzke‐Stollmann & Franck, ).…”
Section: Introductionmentioning
confidence: 99%
“…In capuchins monkey ( Cebus apella ), prosocial tendencies increase with social closeness (de Waal, Leimgruber, & Greenberg, ). In keas ( Nestor notabilis ), when tested in a loose‐string paradigm where birds had to cooperate to obtain a reward, birds cooperated more with affiliates and were also more successful when tested with affiliates than with non‐affiliates (Schwing, Jocteur, Wein, Noë, & Massen, ). In birds, affiliative interactions can be easily measured by recording allopreening and maintenance of close proximity (Seibert, ), as observed in captive groups of spectacled parrotlets ( Forpus conspicillatus ; Garnetzke‐Stollmann & Franck, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, several studies have also now demonstrated that tolerance is indeed an important factor explaining the likelihood and success of cooperation in different animal taxa such as birds (e.g. [4][5][6][7]), carnivores (e.g. [8]) and non-human primates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, if only one end of the string is pulled, the other end becomes inaccessible and the tray cannot be moved forward anymore, rendering the trial unsuccessful. This task has been used with a wide range of species, from ravens to elephants [chimpanzees (27)(28)(29), macaques (30), elephants (31), gray parrots (32), rooks (33), ravens (34), kea (35,36), and dogs (37)], with many succeeding in solving the task after being initially trained individually to pull the tray out by pulling both ends of the rope together.…”
mentioning
confidence: 99%